The Role of Glial Mitochondria in α-Synuclein Toxicity - Jeon, Yu-Mi; Kwon, Younghwi; Jo, Myungjin; Lee, Shinrye; Kim, Seyeon; Kim, Hyung-Jun (Frontiers in Cell and Developmental Biology, 2020)
The abnormal accumulation of alpha-synuclein (α-syn) aggregates in neurons and glial cells is widely known to be associated with many neurodegenerative diseases, including Parkinson’s disease (PD), Dementia with Lewy bodies (DLB), and Multiple system atrophy (MSA). Mitochondrial dysfunction in neurons and glia is known as a key feature of α-syn toxicity. Studies aimed at understanding α-syn-induced toxicity and its role in neurodegenerative diseases have primarily focused on neurons. However, a growing body of evidence demonstrates that glial cells such as microglia and astrocytes have been implicated in the initial pathogenesis and the progression of α-Synucleinopathy. Glial cells are important for supporting neuronal survival, synaptic functions, and local immunity. Furthermore, recent studies highlight the role of mitochondrial metabolism in the normal function of glial cells. In this work, we review the complex relationship between glial mitochondria and α-syn-mediated neurodegeneration, which may provide novel insights into the roles of glial cells in α-syn-associated neurodegenerative diseases.